(untitled) (Annual of the Faculty of Philosophy in Skopje, 2009)
The analyses of relation between attribution of causality and attribution of responsibility for one’s own actions and the actions of others reveals that in many cases perception of causality is key element in making judgments about responsibility. However, the relation between these two attribution phenomena it is not direct and necessary. Attribution of responsibility is more complex process than looking for the causes of actions. When people attribute responsibility, they can use additional criteria and judge responsibility in different ways.